The effects of mulching towards soil physiochemical properties / Hadhinah Hasbullah - Hasbullah, Hadhinah (Faculty of Plantation and Agrotechnology, 2018)
Mulching is a conventional and traditional agricultural practices that helps farmers to improve their yield production and maintaining their agricultural practices. It helps in reducing water usage and conserving the soil moisture. Organic mulching decomposed and supply nutrients towards the soil. This study was conducted at the sharefarm of UiTM Jasin. This study was to determine the effect of organic mulching application towards soil physiochemical properties based on three types of organic mulching application to determine the most suitable and fast decompose mulch in providing a natural and effective way of enriching soil. The type of mulching used were from leaves of banana tree (Musa acuminata ), papaya tree (Carica papaya) and tecoma tree (Tabebuia pentaphylla).The duration between each replicate is two weeks. The infiltration rate of water significant value at P=0.003. The bulk density of the soil is the best at papaya mulch treatment 1.44 g/cm3. The results for highest nutrient content in soil for phosphorus and magnesium is tecoma mulch 319.53 ppm, for potassium is papaya mulch 339.7 ppm and calcium content is banana mulch 380.53 ppm. The value of the soil pH is 6.69. The result shows that the effect of organic mulching application towards the soil has improve the soil physiochemical properties.